PENGARUH RETURN ON ASSET (ROA), RETURN ON EQUITY (ROE), CURRENT RATIO DAN CASH RATIO TERHADAP HARGA SAHAM PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (PERIODE 2019-2021) - Nadia Islavella; Nadia Roosmalitasari Sari (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2022)
The stock price is one of the benchmarks or a sign of a company's financial stability, with a stable stock price it will also make a company still trusted by the public. The purpose of this study is to explore the factors that can affect the stock price of mining companies listed on the IDX during the 2019-2021 period, especially in financial ratios in the form of Return On Assets, Return On Equity, Current Ratio and Cash Ratio of mining companies. An associative quantitative approach is the choice in this study, using multiple linear regression analysis. The results showed that in the Partial T test, each variable Return On Assets, Return On Equity, Current Ratio and Cash Ratio had an effect on stock prices in mining companies. Then in the Simultaneous F test also shows that all variables Return On Assets, Return On Equity, Current Ratio and Cash Ratio together affect stock prices in mining companies. The conclusion in this study, it is important for companies to consider many factors in maintaining stock price stability, as an effort to maintain the company's existence in maintaining public trust as users or consumers.